2010
DOI: 10.2106/jbjs.h.00927
|View full text |Cite
|
Sign up to set email alerts
|

Zone-II Flexor Tendon Repair: A Randomized Prospective Trial of Active Place-and-Hold Therapy Compared with Passive Motion Therapy

Abstract: Active motion therapy provides greater active finger motion than passive motion therapy after zone-II flexor tendon repair without increasing the risk of tendon rupture. Concomitant nerve injuries, multiple digit injuries, and a history of smoking negatively impact the final outcome of tendon repairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 34 publications
6
89
1
2
Order By: Relevance
“…A canine model of joint mobilization following tendon repair found that early motion resulted in fewer adhesions with improved tendon gliding and superior tensile strength compared with postoperative immobilization [120][121][122] . Multiple rehabilitation protocols ranging from those emphasizing passive motion, those that incorporate active finger flexion, and those that incorporate combinations of the two, have been utilized postoperatively and are effective in restoring joint motion 123,124 . Kitis et al found improved grip strength, range of motion, and hand function (Disabilities of the Arm, Shoulder and Hand score 125 ) when patients were treated with active mobilization with a dynamic splinting protocol compared with those treated with a controlled passive movement regimen 126 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…A canine model of joint mobilization following tendon repair found that early motion resulted in fewer adhesions with improved tendon gliding and superior tensile strength compared with postoperative immobilization [120][121][122] . Multiple rehabilitation protocols ranging from those emphasizing passive motion, those that incorporate active finger flexion, and those that incorporate combinations of the two, have been utilized postoperatively and are effective in restoring joint motion 123,124 . Kitis et al found improved grip strength, range of motion, and hand function (Disabilities of the Arm, Shoulder and Hand score 125 ) when patients were treated with active mobilization with a dynamic splinting protocol compared with those treated with a controlled passive movement regimen 126 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…10 We appraised each study and calculated a total MINORS score from a maximum of 16 for noncomparative studies and 24 for comparative studies. Of the studies included, only 2 11,12 were prospective randomized controlled trials. We eval- uated these studies using the Detsky quality score, which is a validated tool to assess the quality of randomized controlled trials.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…A lthough new suture materials [1][2][3] , suture techniques 4,5 , and postoperative rehabilitation protocols 6,7 have improved clinical outcomes, functional restoration following flexor tendon injury and repair in zone II remains a substantial concern for hand surgeons because of the high rate of complications, such as rupture at the repair site and Disclosure: One or more of the authors received payments or services, either directly or indirectly (i.e., via his or her institution), from a third party in support of an aspect of this work. None of the authors, or their institution(s), have had any financial relationship, in the thirty-six months prior to submission of this work, with any entity in the biomedical arena that could be perceived to influence or have the potential to influence what is written in this work.…”
mentioning
confidence: 99%